Independent student leadership: memorized conductorless performance and student autonomy - Toll, Cody (Kansas State University, 2022)
This report demonstrates the results of an emphasis on providing students in a school instrumental program with opportunities to make decisions as a group, to aspire to lofty goals, and to take initiative in pursuit of those goals. In this case, the students pursued the challenge to perform a masterwork entirely from memory and without a conductor. The long-term arc of the school year was to provide the students with the tools to achieve this goal by their final concert. The students were given training in nonverbal communication techniques including breathing, cueing, eye contact, and awareness of each instrument’s function at different moments in the music. Memorization was also a key component, and students gained experience in memorization techniques that included slow-tempo practice, listening, and repetition as individuals, in smaller segments of the ensemble, and as a large group. During pursuit of my Masters’ degree, I have developed a philosophy of teaching music that incorporates a new set of priorities. Providing students with opportunities to set goals that are satisfying and guide them through charting a strategic and logical course to reaching those goals is a key facet of what I hope to achieve with my most capable ensemble. I intend to provide them with the tools to dream big and have confidence in their ability to achieve fulfilling musical experiences. In pursuit of these ambitious goals, it also was important to help students understand the cost of pursuing them – the time, effort, and dedication that would be required to accomplish their aim would mean making sacrifices for the good of the ensemble. The result was for the students to experience a deeper sense of pride and ownership, having collectively performed the role of conductor, and a richer experience of the music having internalized it entirely.
Keywords: Music; Student leadership; Memorization; String orchestra